Students’ Perceptions on the Implementation of Online Learning in Pandemic Era - Homsatul Istiqomah; Mochammad Hatip; Henri Fatkurochman; Fitrotul Mufaridah (Universitas Muhammadiyah Jember, 2021)
The implementation of online learning in Indonesia today becomes an alternative to the conventional learning because of the pandemic situation. However, it triggers some problems during the learning process. The problems exist because of various aspects. One of them is the way how the teachers implement the learning process. This research is aimed to investigate how students perceive the online learning implementation in higher education based on four categories (Planning Promotion, Education, Support Training, and Encouragement). It is descriptive-survey research using a questionnaire as the instrument to collect the data. The result shows various perceptions of students. The average students perceive: 1) implementation of online learning is well planned, 2) the lecturers are competent enough in implementing the online learning, 3) they got sufficient support during the online learning, and 4) the online learning situation encourages them in the learning process. This research result can be used as an evaluation for the stakeholders (lecturers and decision-makers) for the online learning implementation.